The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14194212
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Serum Vitamin D Concentration and New Inflammatory Biomarkers—Systemic Inflammatory Index (SII) and Systemic Inflammatory Response (SIRI)—In Patients with Ischemic Heart Disease

Abstract: The incidence of ischemic heart disease (IHD) increases every year. This cardiovascular disease has an inflammatory factor in its etiology due to different immune cells that influence atherogenesis. New inflammatory biomarkers—the Systemic Inflammatory Index (SII) and the Systemic Inflammatory Response (SIRI)—attempt to describe the pro- and anti-inflammatory balance and quantify the complex impact of the immune system on atherosclerosis, while vitamin D has a multidirectional impact on the human body, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 116 publications
1
15
0
Order By: Relevance
“…These observational studies have examined wide age categories, primarily middle-aged individuals, as homogenous groups without the ability to differentiate prognoses for other age classes, such as the current study's 75-year-old participants. [21,[29][30][31][32] In line with other studies, a study revealed that total and differential WBCs underwent significant alterations during childhood, particularly in the early years. Additionally, as compared to EO#, BASO#, and MONO#, LYMPH# and NEUT# showed more clear age-dependent alterations throughout childhood.…”
Section: [28]supporting
confidence: 82%
“…These observational studies have examined wide age categories, primarily middle-aged individuals, as homogenous groups without the ability to differentiate prognoses for other age classes, such as the current study's 75-year-old participants. [21,[29][30][31][32] In line with other studies, a study revealed that total and differential WBCs underwent significant alterations during childhood, particularly in the early years. Additionally, as compared to EO#, BASO#, and MONO#, LYMPH# and NEUT# showed more clear age-dependent alterations throughout childhood.…”
Section: [28]supporting
confidence: 82%
“…Several investigators have also pointed to the reduction of inflammation by VD in COVID-19 infection as the main mechanism of VD action. In addition, other researchers observed that new biomarkers for inflammation such as the systemic inflammatory index and response were negatively associated with VD concentrations (Dziedzic et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…As emerging biomarkers, the superiority of SII, SIRI and AISI have been identified in numerous diseases, including cancers, cardiovascular diseases, sacroiliitis and diabetic nephropathy [ 9 , 12 , 13 , 18 20 ]. Compared to traditional markers of inflammation, the three systemic inflammation markers are more favorable indicators of inflammatory status and have demonstrated superior predictive power and prognostic value in multiple studies [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%